The Effect of University Partners' Satisfaction and Trust in Relationship Commitment - Sonya Dwi Rachmawati; Heti Mulyati; Megawati Simanjuntak (Jurnal Doktor Manajemen (JDM), 2023)
This study analyzes factors influencing relationship commitment in collaboration with IPB University. A case study in IPB University, this study used survey methods with a questionnaire to 100 respondents. The results identified that satisfaction, communication, and shared value significantly influence trust, while shared value, relationship benefits, and trust significantly influence commitment. Therefore, IPB University shall focus on promoting all six variables to improve collaboration services and trust-building to increase relationship commitment. Shared value can be improved by adding more non-profit-oriented community service programs, while satisfaction can be improved by intensifying collaboration coordination at IPB University, mostly through the Directorate of Collaboration and Alumni Affairs. Enhancing communication can be done through website and social media optimization and information update for collaboration partners, and enhancing relationships can be done by improving human resources and new applicable agriculture technologies.